DESCRIPTION OF STUDENTS' DESIGN THINKING ABILITY BASED ON LEVEL OF CREATIVITY - Gunawan, Gunawan; Mailanufi, Fellya; Kusuma, Jaka Wijaya; Sugihandardji, Chumaedi; Widiyastuti, Erni (International Journal of Multidisciplinary Research and Literature, 2023)
Design thinking can help students think outside the box and develop creativity. This study aims to describe students' design thinking skills based on the level of creativity in class X Merdeka 8 SMA Negeri 1 Purwokerto. The subjects involved in this study were 36 students. The type of research used is qualitative descriptive. The data collection techniques used are written tests, interviews, and documentation. Based on the results of the creativity level test, students are grouped into five levels, namely very creative, creative, quite creative, less creative and not creative. Each level of creativity is chosen by one student using purposive sampling techniques. The results of this study show that students with a very creative and creative level are able to meet the five indicators of design thinking, namely emphatize, define, ideate, prototype, and test. Students with a creative level are able to meet 4 indicators, namely emphatize, define, ideate and prototype. While students with non-creative levels are only able to meet the indicators of emphatize, define, and ideate